ANALISIS PENGARUH RASIO CAMEL DALAM MEMPREDIKSI FINANCIAL DISTRESS PERBANKAN INDONESIA - Kurniasari, Christiana; Ghozali, Imam (Diponegoro Journal of Accounting, 2013)
This research aims to analyze the effect of the CAMEL ratio to predict Indonesian Banks’s financial distress. The CAMEL ratio consist of CAR (capital adequacy ratio), NPL (non performing loan), ROA (return on asset), ROE (return on equity), LDR (loan to deposit ratio), and BOPO (operating expense to operating income). The sample of this research was extracted using purposive sampling method, comprising 120 banks taken from Infobank magazine for the period of 2009, 2010, 2011, 2012. From sample, there are 85 banks, consist of 80 nontrouble banks and 5 trouble banks. The statistic methods used to analyze the hypothesis of this research is logistic regression. The resulst of this research show that CAR, NPL, ROA, and ROE have no significant effect on probability of banks’s  financial distress. LDR and BOPO have significant influences on probability of banks’s financial distress.